Integrating A Corporate Social Responsibility (CSR) Program Into The Business Process - Sudarisman, Antonius; Adam, Subagyo (Opción, 2019)
This study aims at describing a best practice in the implementation of Corpo- rate Social Responsibility (CSR), with a case of how a large mining company helps local contractors to be more effective and efficient in delivering their projects through a project called Integrated Contractor Strategy (ICS). The research employs descriptive approach. The result of the study shows that the use of project-based approach was effective in improving the internal pro- cesses of local contractor engagement as well as in improving the capability of local contractors to deliver their projects more efficiently and in a sustainable manner.